Glycine adsorption on silicon (001) - Ferraz,A. C. (2006)
In this work we employ the state of the art pseudopotential method, within a generalized gradient approximation to the density functional theory, to investigate the dissociative adsorption process of glycine on the silicon surface. Our total energy calculations indicate that the chemisorption of the molecule is as follow. The gas phase NH2-C2H2-OOH adsorbs molecularly to the electrophilic surface Si atom and then dissociates into NH2-C2H2-OO and H, bonded to the electrophilic and nucleophilic surface silicon dimer atoms respectively, with an energy barrier corresponding to a thermal activation that is smaller than the usual growth temperature, indicating that glycine molecules will be observed in their dissociated states at room temperature. This picture is further support by our calculated vibrational modes for the considered adsorbed species.